Integrating the MERDEKKA Intervention into Palliative Care for Tuberculosis Patients: A Mixed-Methods Study - Astuti, Ni Luh Seri; Rismayanti, I Dewa Ayu; Pratama, Aditha Angga (Babali Nursing Research, 2025)
Introduction: In Indonesia, pulmonary tuberculosis causes more than 95% of mortality. WHO has established a target for treating tuberculosis that is aligned with Asta Cita 4, which specifies that Indonesia would be TB-free by 2030. Palliative care does not only mean end-of-life care. Methods: mixed methods sequential explanatory design. Quantitative data was first collected using a one-group pre- and post-test design, and the qualitative analysis using in depth interview. Merdekka Intervention using RESPECT instrument and 80 sample in pre post test. also 15 participant to explore the experience after doing MERDEKKA intervention. Result: The majority of respondents (35.8%) were aged 62 to 72, largely male (96.1%), and had completed junior high school (43.5%). The majority of respondents were farmers (48.7%), had tuberculosis in their family (96.1%), and had been on treatment for at least 6 months. The MERDEKKA intervention had a substantial impact on TB patients' knowledge and attitudes, with a p-value of 0.001 for knowledge and 0.003 for attitudes. The effect size value was larger than 1.0, indicating a very powerful influence. Patients' experiences after the MERDEKKA intervention are described in three themes: Developing good trust between the patient and the nurse, providing proper and necessary care, and being enthusiastic about healing within six months Conclusion: The palliative care model, including the MERDEKKA intervention, is critical in the care of TB patients. Even though it is not in the terminal phase, its presence in the initial phase of therapy can improve the patient's health in all aspects of need.